Fatigue degradation after salt spray ageing of electromagnetically riveted joints for CFRP/Al hybrid structure. (15th March 2018) - Jiang, Hao; Cong, Yanjun; Zhang, Xu; Li, Guangyao; Cui, Junjia
Abstract: The durability of hybrid carbon fiber reinforced plastics (CFRP)/aluminum alloy (Al) structures is receiving increasing attentions in engineering applications. In this paper, the mechanical performance of CFRP/Al electromagnetically riveted lap joints after exposure in neutral salt spray environment for various ageing time was studied. The shear and fatigue tests were conducted. The mechanical property degradation laws and failure mode evolution were obtained. The results showed that the shear and fatigue properties of the CFRP/Al electromagnetically riveted lap joints linearly decreased with the increase of ageing time. In addition, the fatigue test results showed that three weeks was the critical ageing time for failure mode changing. Fatigue crack initiated from the riveted hole (below 3 weeks) and the edge of the overlapping region (over 3 weeks) of Al sheet, respectively. Meanwhile, the fracture analysis showed that the cracks of specimens after long-time ageing (over 3 weeks) were initiated from the several corrosion pits simultaneously. Graphical abstract: Unlabelled Image Highlights: The shear properties after salt spray ageing of CFRP/Al electromagnetic riveted joints were investigated. The relationship between fatigue behaviors and ageing time for CFRP/Al electromagnetic riveted joints were established. The fatigue properties degradation laws after salt spray ageing of CFRP/Al electromagnetic riveted joints were obtained. The fatigue fracture appearances after short-time and long-time ageing were respectively analyzed.